Operational readiness and airport transfer (ORAT) of Kuala Lumpur air traffic control centre (KL ATCC) - Fairolazizi, Muhammad Aiman Zhafran; Rosly, Nurhayati; Jabbar, Balasem Abdulameer (FAZ Publishing, 2019)
The study was conducted in order to find out the implementation of Operational Readiness and Airport Transfer (ORAT) towards the new Kuala Lumpur Air Traffic Controller Centre (KL ATCC) that will restructure the Kuala Lumpur Flight Information Region (KL FIR). The study adopted a qualitative case design and will only focus on the new KL ATCC that expected to finish at the end of Year 2020. The study aimed to interpret the procedure involving ORAT operation while at the same time to investigate on the Malaysia readiness of implementing ORAT and lastly to propose suitable model to implement ORAT effectively. This research was investigated by using qualitative research techniques which questionnaires are taken and adapted as data collection instrument. Descriptive statistics such percentage and graph were used to describe the research findings. The result of this study showed that the most crucial category that need to be emphasized in ORAT element for KL ATCC is System Readiness where it was the highest concerns compared to other elements. The study concluded that Malaysia is still at a worried stage in terms of implementing ORAT because all of the categories went above 50%. So Malaysia’s government can implement ORAT for any future project that will benefit on leading to project success.